Starfire : a novel - Brown, Dale, 1956- (William Morrow, 2014)
"With the death of his heroic father, bomber and space warfare veteran Patrick McLanahan, Bradley McLanahan must now fly solo, leading a team of young engineers designing Starfire, the world's first orbiting solar power plant. Starfire will not only deliver unlimited and inexpensive electricity anywhere on planet Earth, it can also transmit power to the moon, and even to spacecraft and asteroids. It's a crucial first step in the exploration of the solar system, and Bradley and his team are on the cutting edge. But U.S. president Kenneth Phoenix's plans to militarize and industrialize Earth's orbit sparks an arms race in space that eclipses the darkest and most terrifying days of the Cold War. Before he can prevent it, Bradley and his team are caught at the center of a battle that threatens to become an all-out global conflict for control of space" --